Human Identity Rediscovery in Jojo Moyes’ Me Before You: Psychoanalysis Theory - Pramana, Dennis Audria; Haryanti, Rahayu Puji (Universitas Negeri Semarang, 2024)
Human identity can play important role to determine the purpose of life. The absence of identity can be lost and cause conflict in both within individual the human being himself or with the people around him. Jojo Moyes’ romance novel “Me Before You” explores the theme of the people around him. This loss of human identity is represented in the romance novel Me Before You by Jojo Moyes. Therefore, this study aims to analyze more deeply the psychological problems of the main character in the novel that contribute to the loss of his identity and how the character subsequent effort to rediscover identity again. The research employs qualitative method by applying Sigmund Freud's psychoanalysis theory, especially about the Oedipus complex. The study uncovers two psychological phases experienced by the main character through textual analysis data is obtained based on the analysis of sentences, phrases, and words in the novel. Me Before You novel presents two psychological phases experienced by the main character, namely the phase of identity loss and the phase of finding his identity again. The novel shows the impact of the identity loss of identity: leads to emotions of feeling pessimistic, useless, and experiencing changes in character. The process of rediscovering the main character's identity is rediscovered by the arrival of someone who is a subconscious true love and who is a person's true identity. Unconsciously, the process of fulfilling the protagonist's primitive desires goes smoothly due to the superego’s balancing mechanism. This allows works well so that the ego is able to satisfy id's desires while maintaining self-safety through the projection of love for the mother with a figure who has a resemblance to her.